2014
DOI: 10.1016/j.micres.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidative activity of extracts and essential oils of Myrtus communis L.

Abstract: Since synthetic antimicrobial agents and food additives can cause a number of adverse effects, there is a growing interest from consumers in ingredients from natural sources. Medicinal plants, such as Myrtus communis L. are a source of new compounds which can be used in both the food industry and for medical purposes, primarily as antimicrobial agents. In this review, the characteristics of myrtle essential oils and extracts are summarized, with particular attention to their chemical composition, biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
203
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(216 citation statements)
references
References 145 publications
7
203
0
6
Order By: Relevance
“…35,36 Myrtus communis L. from the Myrtaceae family, generally known as myrtle, is an evergreen shrub and aromatic herb with rough bark and hastate, linear, and thick leaves, being used extensively worldwide. 37 It has traditional culinary and medicine uses. [37][38][39] Recently, it was shown that the myrtle plant contains many antioxidant components that can be used as reductant agents in biosynthesis of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Myrtus communis L. from the Myrtaceae family, generally known as myrtle, is an evergreen shrub and aromatic herb with rough bark and hastate, linear, and thick leaves, being used extensively worldwide. 37 It has traditional culinary and medicine uses. [37][38][39] Recently, it was shown that the myrtle plant contains many antioxidant components that can be used as reductant agents in biosynthesis of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…37 It has traditional culinary and medicine uses. [37][38][39] Recently, it was shown that the myrtle plant contains many antioxidant components that can be used as reductant agents in biosynthesis of metal nanoparticles. 39 Silver nanoparticles were synthesized in the present study using M. communis L. leaf extract, then tested against various Gram-positive and Gram-negative strains.…”
Section: Introductionmentioning
confidence: 99%
“…Myrtle extract promotes a well oxygenated, stress free complexion capable of neutralizing the effects of pollutants, and free radical damage [39].…”
Section: Use Of Anti-oxidantsmentioning
confidence: 99%
“…Since synthetic antimicrobial drugs can cause a number of negative side effects, medicinal plants are proved to be effective, cheap and safe source of natural antimicrobial agents [13]. In addition, plants are also rich with flavonoids which are considered excellent source of antioxidants due to their advantages as hydrogen donor, reducing agent, and singlet oxygen scavenger.…”
Section: Introductionmentioning
confidence: 99%